Diagnostic Performance of Iterative Reconstruction of Cone-beam Computed Tomography for Detecting Vertical Root Fractures in the Presence of Metal Artifacts - Barros-Costa, Matheus; Santaella, Gustavo; Oliveira-Santos, Christiano; Freitas, Deborah Queiroz; Scarfe, William C; Groppo, Francisco Carlos (Journal of endodontics, 2025)
Vertical root fractures (VRFs) are challenging to detect, especially in endodontically treated teeth. Cone-beam computed tomography (CBCT) has improved VRF detection over periapical radiography but is limited by metal artifacts. Iterative Reconstruction (IR) algorithms are an alternative to the traditional Filtered-Back Projection (FBP) and have been shown to reduce image noise due to metal artifacts. This study aimed to evaluate the impact of IR on VRF detection in the presence of metal artifacts from intracanal materials and/or adjacent implants. This ex-vivo study included 22 single-rooted teeth (10 fractured, 12 nonfractured) placed in a human mandible phantom. CBCT scans were performed using Midmark EIOS CBCT with both reconstruction methods (FBP and IR), with and without metal artifact reduction (MAR) tool activation. Clinical conditions included the presence or absence of gutta-percha and adjacent titanium dental implants. Five oral radiologists evaluated the anonymized images for VRF presence using a 5-point scale. Diagnostic accuracy, sensitivity, specificity, and intra- and interobserver agreement were assessed using receiver operating characteristic curves and multiway ANOVA. The area under the curve values ranged from 0.60 to 0.85, with no significant differences between reconstruction methods (P > .05). Sensitivity and specificity were generally unaffected by reconstruction method or MAR activation (P > .05), except when MAR reduced sensitivity in FBP with gutta-percha (P < .05). Metal artifacts from gutta-percha and implants negatively impacted VRF detection. The reconstruction method did not significantly influence VRF detection, suggesting that either method can be used in clinical practice without compromising diagnostic accuracy, even in the presence of metal artifacts.